2021
DOI: 10.1177/00938548211010315
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Individual Defiance of COVID-19 Pandemic Mitigation Strategies: Insights From the Expanded Model of Deterrence and Protection Motivation Theory

Abstract: The governmental responses to the COVID-19 pandemic include concerns for both public health and formal social control. Government leaders asked the public to help mitigate the spread of the virus by adopting various protective behaviors. Our purpose was to evaluate and explain defiance of COVID-19 mitigation strategies, drawing from the expanded model of deterrence and protection motivation theory. A national sample of 600 American adults were surveyed about perceptions of, and behaviors during, the early part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
3
13
0
Order By: Relevance
“…Our findings are consistent with the results from previous studies, which demonstrated a positive association between fear of COVID-19 or perceived threat of COVID-19 and people’s compliance and protective behaviors (Burruss et al, 2021 ; Harper et al, 2020 ; Kuiper et al, 2020 ; McCarthy et al, 2021 ; Oosterhoff et al, 2020 ; Van Rooij et al, 2020 ). Thus, even though fear represents a form of negative emotion that tends to pose risks to people’s long-term wellbeing, our findings suggest that it has an effect of quickly and sufficiently motivating individuals to adopt protective behaviors and comply with public rules to minimize the risks of infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with the results from previous studies, which demonstrated a positive association between fear of COVID-19 or perceived threat of COVID-19 and people’s compliance and protective behaviors (Burruss et al, 2021 ; Harper et al, 2020 ; Kuiper et al, 2020 ; McCarthy et al, 2021 ; Oosterhoff et al, 2020 ; Van Rooij et al, 2020 ). Thus, even though fear represents a form of negative emotion that tends to pose risks to people’s long-term wellbeing, our findings suggest that it has an effect of quickly and sufficiently motivating individuals to adopt protective behaviors and comply with public rules to minimize the risks of infection.…”
Section: Discussionsupporting
confidence: 93%
“…A Dutch study (Kuiper et al, 2020 ) and a US study (Van Rooij et al, 2020 ) found that the perceived threat of COVID-19 predicted better compliance behavior. Another recent US study (Burruss et al, 2021 ) also found a link between fear of COVID-19 and compliance with pandemic rules. The study showed that rational choice considerations, including the perceived severity of the disease, certainty about dying from it, and how much perceived control that one has over getting it predicted fear of COVID-19, which, in turn, predicted compliance with COVID-19 mitigation guidelines along with rational choice considerations.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Possible responses ranged from 1 (Always) to 5 (Never). These items were used to create the latent factor for defiance, with a higher score indicating more non-compliance with federal CDC guidelines (Burruss et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Some of this work has focused on instrumental considerations. Burruss et al (2021) found that perceived disease severity, certainty of death associated with the virus, and control over the spread of the COVID-19 virus resulted in heightened fear, which ultimately increased compliance with COVID-19 mitigation behaviors (see also Al-Sabbagh et al, 2021). These findings are further supported by several recent studies concluding that fear, perceived health risk, and perceived control of the coronavirus are associated with more compliance with mitigation guidelines (e.g., Brouard et al, 2020; Harper et al, 2020; McCarthy et al, 2021; Wise et al, 2020).…”
Section: Research On Individual Compliance With Disease Mitigation St...mentioning
confidence: 99%
“…Their paper focuses on China, a country in which the police were viewed as the last resort for the enforcement of such restrictive measures, while in other countries around the world the police were the primary enforcers of the newly developed rules restricting citizens’ behavior in response to the pandemic. Extant research indicates that the fear of being infected with COVID-19 enhances citizens’ decisions to obey restrictive measures (e.g., Burruss et al, 2021 ; Van Rooij et al, 2020 ). Shen and colleagues’ paper pushes the issue farther as the authors add measures of pandemic stress and peer influence, as well measures of perceived frequency of police presence and evaluations of police competence into the models.…”
mentioning
confidence: 99%